A Successful Population Policy: Potentials and Constraints (Distinguishedl Lecture) (The Pakistan Development Review, 1993)
The current rapid population growth in many developing countries is the result of an historical process in the course of which mortality rates have fallen significantly but birthrates have remained constant or fallen only slightly. Whereas, in industrial countries, the drop in mortality rates, triggered by improvements in nutrition and progress in medicine and hygiene, was a reaction to economic development, which ensured that despite the concomitant growth in population no economic difficulties arose (the gross national product (GNP) grew faster than the population so that per capita income (PCI) continued to rise), the drop in mortality rates to be observed in developing countries over the last 60 years has been the result of exogenous influences: to a large degree the developing countries have imported the advances made in industrial countries in the fields of medicine and hygiene. Thus, the drop in mortality rates has not been the product of economic development; rather, it has occurred in isolation from it, thereby leading to a rise in population unaccompanied by economic growth. Growth in GNP has not kept pace with population growth: as a result, per capita income in many developing countries has stagnated or fallen. Mortality rates in developing countries are still higher than those in industrial countries, but the gap is closing appreciably. Ultimately, this gap is not due to differences in medical or hygienic know-how but to economic bottlenecks (e.g. malnutrition, access to health services)